LIFE AND ITS VALUE: A MEDICAL PERSPECTIVE - Prakash , Om (Journal of Dharma, 1996)
Practice of medicine and teaching graduate students in medicine are my vocations. I believe that this profession affords abundant opportunity for the observation of human behaviour and its varied manifestations. After all, the healing profession allows people in various states of distress to be scrutinised and the doctor interested in the human condition is in a unique position to appreciate nuances and think about the meaning and value of life. I shall portray some of the ideas that have struck me as rather important in the context of the title of this article.